Designing Lifelong Language Learning Programs for Working Adults Through Mobile Learning - Abraham Berhe; Theo Ghirard; Titi Latu (International Journal of Language and Ubiquitous Learning, 2025)
Background. The increasing demand for continuous professional development among working adults has emphasized the need for flexible, accessible, and sustainable language learning opportunities. Traditional classroom-based instruction often fails to accommodate adult learners who face constraints related to time, location, and work schedules. Purpose. This study aimed to design and evaluate a lifelong language learning program for working adults through mobile learning platforms. It specifically examined the pedagogical, technological, and motivational factors that support sustained learner engagement and long-term language retention. Method. A mixed-method research design was employed involving 150 working professionals from various industries in Jakarta. Quantitative data were collected through pre- and post-tests and learner engagement analytics, while qualitative data were obtained from semi-structured interviews and learner diaries. Results. The results demonstrated significant improvements in participants’ vocabulary acquisition, communication confidence, and long-term language retention following the mobile learning intervention. Qualitative findings revealed that personalized content, task relevance to professional contexts, and mobile accessibility were key factors in sustaining learner engagement over time. Conclusion. The study concludes that mobile-assisted lifelong language learning programs provide an effective and scalable approach to adult language education.